Telework and Lifelong Learning - Bjursell, Cecilia; Bergmo-Prvulovic, Ingela; Hedegaard, Joel (Frontiers in Sociology, 2021)
The increase of telework during the pandemic is predicted to impact working life, not only in terms of a larger number of employees working from home, but more importantly it may transform the way we conceptualize work. This will in turn impact systems and participation in lifelong learning, and there is a risk for increased social inequalities as neither telework nor lifelong learning is evenly distributed among workers. Statistics on telework in the EU show that there are differences between age groups, nations, sectors and professions. If these trends will steer forward, there is a risk for widening gaps between countries, companies and workers. To establish the current knowledge base, we have made a synthesis of reviews from several disciplines. One finding is that the previous literature on telework has not included lifelong learning in any form (formal, non-formal and informal). Based on the review of previous studies, the paper suggests a number of research questions for future research. This is relevant as research about telework and lifelong learning has the potential to contribute to a sustainable working life in terms of providing more flexible arrangements for employees and to support the lifelong learning that takes place in contexts such as the office, home, online meetings, and in virtual reality.